Think Hard or Think Smart: Network Reconfigurations After Divergent Thinking Associate With Creativity Performance - Wu, Hong-Yi; Kuo, Bo-Cheng; Huang, Chih-Mao; Tsai, Pei-Jung; Hsu, Ai-Ling; Hsu, Li-Ming; Liu, Chi-Yun; Chen, Jyh-Horng; Wu, Changwei W. (Frontiers in Human Neuroscience, 2020)
Evidence suggests divergent thinking is the cognitive basis of creative thoughts. Neuroimaging literature using resting-state functional connectivity (RSFC) has revealed network reorganizations during divergent thinking. Recent studies have revealed the changes of network organizations when performing creativity tasks, but such brain reconfigurations might be prolonged after task and be modulated by the trait of creativity. To investigate the modulation, 40 young participants were recruited to perform consecutive Alternative Uses Tasks (AUTs) for divergent thinking and two resting-state scans (before and after AUT) were used for mapping the brain reorganizations after AUT. We split participants into high- and low-creative groups based on creative achievement questionnaire (CAQ) and targeted on reconfigurations of the two brain networks: (1) default-mode network (DMN) and (2) the network seeded at the left inferior frontal gyrus (IFG) because the between-group difference of AUT-induced brain activation located at the left IFG. The changes of post-AUT RSFCs (DMN and IFGN) indicated the prolonged effect of divergent thinking. More specifically, the alterations of RSFCIFG-AG and RSFCIFG-IPL (AG: angular gyrus, IPG: inferior parietal lobule) in the high-creative group had positive relationship with their AUT performances (originality and fluency), but not found in the low-creative group. Furthermore, the RSFC changes of DMN did not present significant relationships with AUT performances. The findings not only revealed the transient neuroplasticity following divergent thinking, but also suggested the distinct IFGN reconfiguration between individuals with different creativity levels.